How can organizational communication impact society? Reflections from the communication practice in Portuguese communication - Carareto, Mariana [UNESP]; Andrelo, Roseane [UNESP]; Ruao, Teresa (Univ Malaga, Inst Investigacion Relaciones Publicas, 2022)
This investigation(4) aims to reflect on the impact generated by organizational communication in society, considering its capacity to interfere in the public sphere construction, through the perspective of Portuguese communication professionals. For this, supported by a theoretical perspective of organizational communication and communication for development, in-depth interviews were conducted with communication agencies. To understand the impact, results interactional context and the discourse influence in individuals' perceptions and behaviors.
Keywords: Organizations; Organizational communication; Impact; Society